(untitled) (Revista BOEM, 2024)
In this study we analyzed two videos published at the Festival of Digital Videos and Mathematics Education (FVDEM), with an emphasis on the probabilistic concepts presented. In addition to analyzing these videos, the objective was to investigate the impact of FVDEM as a platform to promote Mathematics Education, recognizing videos as valuable teaching tools. Using a qualitative approach, the videos were analyzed as examples of how Digital Technologies (DT) can promote student autonomy and deepen learning. It is crucial to highlight the importance of the interaction between human beings and digital media in the creation and dissemination of knowledge, highlighting the active role of videos in this process. Thus, the Digital Video Festival not only contributes to students’ understanding of probability, but also empowers them as participatory agents in the construction of mathematical knowledge, demonstrating the transformative potential of DT in Mathematics Education. This approach emphasizes the relevance of videos as dynamic and accessible teaching tools, capable of engaging students and promoting a deeper understanding of mathematical and statistical concepts.